Королева без башни: [роман] / Дарья Донцова - Донцова Даpья Аpкадьевна (Иронический детектив, 2019)
Экземпляры: Ф. 10 (20200617) / Инвентарный номер: 47855 / Цена: 102.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Д 67 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44